Predictors of Near-Infrared Spectroscopy-Detected Lipid-Rich Plaques by Optical Coherence Tomography-Defined Morphological Features in Patients With Acute Coronary Syndrome - Usui, Eisuke; Yonetsu, Taishi; Ohmori, Mari; Kanno, Yoshinori; Nakao, Masahiko; Niida, Takayuki; Matsuda, Yuji; Matsuda, Junji; Umemoto, Tomoyuki; Misawa, Toru; Hada, Masahiro; Hoshino, Masahiro; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Near-infrared spectroscopy (NIRS) provides the localization of lipid-rich components in coronary plaques. However, morphological features in NIRS-detected lipid-rich plaques (LRP) are unclear. Methods A total of 140 de novo culprit lesions in 140 patients with the acute coronary syndrome (ACS) who underwent NIRS and optical coherence tomography (OCT) examinations for the culprit lesions at the time of percutaneous coronary interventions were investigated. We defined a NIRS-LRP as a lesion with a maximum lipid core burden index of 4 mm [LCBI4mm] > 500 in the culprit plaque. Clinical demographics, angiographic, and OCT findings were compared between the patients with NIRS-LRP (n = 54) vs. those without NIRS-LRP (n = 86). Uni- and multivariable logistic regression analyses were performed to examine the independent OCT morphological predictors for NIRS-LRP. Results Clinical demographics showed no significant differences between the two groups. The angiographic minimum lumen diameter was smaller in the NIRS-LRP group than in the non- NIRS-LRP group. In OCT analysis, the minimum flow area was smaller; lipid angle, lipid length, the prevalence of thin-cap fibroatheroma, and cholesterol crystals were greater in the NIRS-LRP group than in the non-NIRS-LRP group. Plaque rupture and thrombi were more frequent in the NIRS-LRP group, albeit not significant. In a multivariable logistic regression analysis, presence of thin-cap fibroatheroma [odds ratio (OR): 2.56; 95% CI: 1.12 to 5.84; p = 0.03] and cholesterol crystals (OR: 2.90; 95% CI: 1.20 to 6.99; p = 0.02) were independently predictive of NIRS-LRP. Conclusions In ACS culprit lesions, OCT-detected thin-cap fibroatheroma and cholesterol crystals rather than plaque rupture and thrombi were closely associated with a great lipid-core burden.